Effects of conceptualizations of forgiveness on specific and dispositional forgiveness - Prieto Ursúa, María; Jódar Anchía, Rafael; Martínez Díaz, María Pilar; Carrasco Galán, María José; Gismero González, María Elena; Cagigal de Gregorio, Virginia (My University)
p

This paper analyzes how a sample of the general population conceptualizes forgiveness, how these beliefs relate to forgiveness and how the results can be used to draw implications for mental health counselors. 147 adults from general population participated in the study. A unilateral concept of forgiveness shows a positive and significant relation with all the types of forgiveness except self-forgiveness, whereas a bilateral understanding of forgiveness, to require the repentance of the offender, the belief in unforgivable offenses and believing that not everybody has the right to forgive any offense lead to decrements in the level of forgiveness.
Artículos en revistas